Role of proteases in the response of plants to drought - D'Ippólito, Sebastián (2021)
Plants are sessile organisms that, to survive they develop response mechanisms under water deficit conditions. Plant proteases play an essential role in a diversity of biological processes, among them tolerance to drought stress. Proteolysis is a critical regulator of stomatal development. Plant proteases are involved in the crosstalk among phytohormones and adjustment of stomatal aperture. Plant proteases are also related to the increment in reactive oxygen species (ROS) production detected in the plant biochemical response to drought. Plant proteases mitigate this process by degrading damaged, denatured, and aggregated proteins, remobilizing amino acids, and generating molecules involved in signal transductions. Although many roles for proteases have been proposed, molecular bases that regulate these mechanisms remain unknown. In this review, we summarize the current knowledge on the participation of proteases in the signaling pathways of plants in response to water deficit and their relationship with plant stress tolerance.